ARE INNOVATION AND INTERNATIONALIZATION INTERTWINED? A QUANTITATIVE STUDY OF THE IMPACT OF THE TYPES OF PROGRAMS IN ELITE BUSINESS SCHOOLS (Proceedings of the International Conference on Education, 2021)
Although relevant pieces of literature discuss innovation in management education and the importance of internationalization of business schools, there is a lack of scholarly articles analyzing the mutual influence between internationalization and innovation in business schools, particularly when considering the types of programs and their location. Henceforth, to fill the identified theoretical gap, this article pursues the following research question: Are innovation and internationalization intertwined in elite business schools? The study follows a two-step methodology in its investigation and experiments. First, we performed a correlational analysis using linear regression (OLS) to determine if there is a relationship between internationalization and innovation of business schools by considering two types of programs: the Global MBA, and the Executive MBA. The results of the OLS method show that there is no correlation between Innovation and Internationalization in the Global MBA programs (p=.546) whereas, there exists a positive correlation between Innovation and Internationalization in Executive MBA (p=.00). Second, we conducted a One-way multivariate analysis of variance (MANOVA) to evaluate the impact of the location of the MBA programs on internationalization and innovation. We found that location presented no significant relationship with internationalization and innovation in the Global MBA program (as their significance levels were p=.483 and p=.490, respectively) and Executive MBA programs (p=.222 and p=.654, respectively). In both cases, these results mean that internationalized or highly innovative programs such as Global MBA and Executive MBA programs can be found all over the world. Thus, we reached two main sets of conclusions. First, innovation and internationalization are uncorrelated in Global MBA programs, whereas both variables (innovation and internationalization) are correlated in Executive MBA programs. For the second set of conclusions, we note that the location of business schools does not impact their internationalization and innovation.
Keywords: Educational Innovation; Internationalization; Executive Education